Irisin in the modulation of bone and cartilage homeostasis: a review on osteoarthritis relief potential - Zhang, Mengtong; Xiong, Wengieng; Qiao, Ruohan; Li, Minhan; Zhang, Chuhan; Yang, Chi; Zhu, Yan; He, Jiaying; Ma, Zhigui (Frontiers in Physiology, 2025)
Osteoarthritis, a progressive and degenerative joint disease, disrupts the integrity of the entire joint structure, underscoring the urgency of identifying more effective therapeutic strategies and innovative targets. Among these, exercise therapy is considered a key component in the early management of osteoarthritis, functioning by stimulating the secretion of myokines from the skeletal muscle system. Irisin, a myokine predominantly secreted by skeletal muscle during exercise and encoded by the FNDC5 gene, has garnered attention for its regulatory effects on bone health. Emerging evidence suggests that irisin may play a protective role in osteoarthritis by promoting tissue homeostasis, enhancing subchondral bone density and microstructure, and inhibiting chondrocyte apoptosis. By improving chondrocyte viability, preserving extracellular matrix integrity, and maintaining homeostasis in osteoblasts, osteoclasts, and osteocytes, irisin emerges as a promising therapeutic target for osteoarthritis. This review delves into the role of irisin in osteoarthritis pathogenesis, highlighting its influence on cartilage and bone metabolism as well as its dynamic relationship with exercise. Additionally, this review suggests that further exploration on its specific molecular mechanisms, optimization of drug delivery systems, and strategic utilization of exercise-induced benefits will be pivotal in unlocking the full potential of irisin as a novel intervention for osteoarthritis.